Fruit and Vegetable Waste Characteristics and Management Practices at Pasig Mega Market in Pasig City, Philippines - Buhion, Ruth Paula; Barrion, Aimee Sheree; Lanorio, Ma. Cristina (Food, Agriculture and Natural Resources - NETWORKS, 2024)
The fruit and vegetable sector produce waste significantly, causing social, environmental, and economic loss. Thus, a study was conducted at Pasig Mega Market, Pasig City to describe the fruit and vegetable vendors' waste management practices. Vendors and government employees participated in focus group discussions and key informant interviews. Results showed an average of 100-200 kilograms of waste were collected in the market daily, with leafy vegetables, watermelon, melon, and saba as common types. Focus group discussions revealed that discounted prices for suboptimal items, quality assurance methods, adherence to First-In-First-Out principles, and marketing strategies were the vendors' efforts to reduce waste. The identified approaches in handling wastes were, giving them as animal feed, creating alternative products, and returning damaged products to suppliers. Key informant interviews disclosed that the local government and market administration practices in waste management were composting and donation as animal feed for the local zoo. Moreover, it revealed improvement in the management of implementing the ordinances. Problems encountered were focused on supplier issues, weather, market competition, and consumer preferences. Overall, their waste management reduces food waste disposed of in landfills. Recommended strategies for vendors and administration are valorizing food waste, organizing awareness and livelihood programs, and conducting regular evaluations.